The evolution of the therapeutic concept ‘GIP receptor antagonism’ - Koefoed-Hansen, Frederikke; Helsted, Mads Marstrand; Kizilkaya, Hüsün Sheyma; Lund, Asger Bach; Rosenkilde, Mette Marie; Gasbjerg, Lærke Smidt (Frontiers in Endocrinology, 2025)
Glucose-dependent insulinotropic polypeptide (GIP) is an intestinal hormone that potentiates glucose-induced insulin secretion in the postprandial state. GIP exerts a broad range of other physiological actions e.g. in the pancreas, bone tissue, and vasculature. In more than 20 years, GIP receptor antagonism has contributed to the discoveries of the role of GIP within both human and animal physiology. In 1986, a fragment of the biological active bovine GIP(1-42), was discovered and characterized as the first GIP receptor antagonist. Several different molecules have been identified, including peptides, vaccines against GIP, GIP antibodies, and antibodies against the GIP receptor. Today, GIP receptor antagonists are not only used as scientific tools but due to significant metabolic effects, they also have a therapeutic purpose. The beneficial clinical effects of GIP receptor antagonism are supported by comparable phenotypic traits of individuals with loss-of-function genetic receptor variants. Novel insights into GIP receptor targeting treatment reveal that both GIP receptor antagonists and agonists, when combined with glucagon like peptide 1 (GLP-1) receptor activation, are associated with improved glycemic control and weight loss. This paradoxical scenario highlights the complexity of GIP receptor pharmacology. Moreover, the long-term effects of therapeutic GIP receptor antagonism in humans are not fully elucidated and are thought to depend on the specific drug molecule, receptor functions, and the extent of GLP-1 receptor activation. With this review, we provide an overview of the preclinical and clinical evidence of GIP receptor antagonism from the central early findings to the current therapeutics in clinical development. Finally, the current therapeutic developments and the further therapeutic potential within GIP receptor antagonism are discussed.